An investigation on the thermal energy storage in an enclosure packed with micro-encapsulated phase change material. (June 2021) - Ho, C.J.; Siao, Chun-Ruei; Yang, Tien-Fu; Chen, Bo-Lin; Rashidi, Saman; Yan, Wei-Mon
Abstract: -This study aims to focus on the unsteady heat storage in an air-saturated container filled with micro-encapsulated phase change material (MEPCM) particles. Based on the obtained results, the use of the phase change capsules would increase the thermal storage rate in the cavity and prevent its loss. As indicated by the obtained findings, the temperature of the cold-surface has a significant influence on the heat transfer behavior so that in the case without phase change, the heat is transferred from the cold- and hot-surfaces via the convection and conduction mechanisms until it reaches a steady-state value. On the other hand, in the case of phase change material, a portion of the heat transferred from the hot surface to the cold surface is spent on the phase change process due to the latent heat of melting and yields a higher value of the net thermal storage in the cavity. The time needed for the stabilization of the container during the heat storage process, Fo ss, increases with decreasing the temperature difference between the hot and cold surfaces. In addition, it takes longer time for the stabilization of the container as the temperatures of the hot and cold surfaces decreases.